2011
DOI: 10.1103/physrevb.84.014506
|View full text |Cite
|
Sign up to set email alerts
|

Structural evidence for an edge-contaminated vortex phase in a Nb crystal using neutron diffraction

Abstract: We report the first direct observation of a disordered vortex matter phase existing near the edge of a bulk type-II superconductor Nb using a novel position-sensitive neutron diffraction technique. This "edge-contaminated" vortex state was implicated in previous studies using transport techniques and was postulated to have played a significant role in the behavior of vortex dynamics in a wide range of type-II superconductors. It is found that upon thermal annealing, the vortex matter in the bulk undergoes reor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…In addition to a transport current or an AC field, an ordering of the VL can in some cases be achieved by a simple thermal cycling (Daniilidis et al, 2007;Marziali Bermudez et al, 2017). Conversely, the application of a field oscillation will introduce an edge "contamination" of the VL at surfaces where vortices enter and leave the sample (Hanson et al, 2011). While FIG.…”
Section: Relating Structural and Dynamic Propertiesmentioning
confidence: 99%
“…In addition to a transport current or an AC field, an ordering of the VL can in some cases be achieved by a simple thermal cycling (Daniilidis et al, 2007;Marziali Bermudez et al, 2017). Conversely, the application of a field oscillation will introduce an edge "contamination" of the VL at surfaces where vortices enter and leave the sample (Hanson et al, 2011). While FIG.…”
Section: Relating Structural and Dynamic Propertiesmentioning
confidence: 99%
“…[17]). A weak pinning 17 excludes also an influence of the peak effect [32][33][34] on the measured field distributions. The BCS-Gor'kov model breaks down for T ≤ 0.5 K as shown by the dasheddotted lines in Fig.…”
mentioning
confidence: 99%
“…Eventually, vortex entanglement and the proliferation of VL dislocations increase the effective pinning, producing a sudden rise of the critical current J c known as the Peak Effect (PE) [7,8], which is the fingerprint of the ODT in vortex matter. While both the highpinning disordered phase and the low-pinning ordered phase, above and below the ODT, are widely accepted in the literature, intermediate responses have been ascribed to surface contamination and partial reordering by the probing transport current [9,10,13,14]. However, in the narrow transitional region adjacent to the PE, for which a multidomain phase has been theoretically proposed [15], non-invasive techniques have shown that pinning can be partially decreased or even increased by applying dc currents [16,17] To address this question, we performed an experiment in a clean NbSe 2 single crystal, combining small angle neutron scattering (SANS) with in-situ linear ac susceptibility measurements.…”
mentioning
confidence: 99%